Determinants of adherence and effects on health-related quality of life after myocardial infarction: a prospective cohort study - Gundula Krack (BMC Geriatrics, 2018)
Abstract Background Adherence to recommendations and medication is deemed to be important for effectiveness of case management interventions. Thus, reasons for non-adherence and effects on health-related quality of life (HRQoL) should be fully understood. The objective of this research was to identify determinants of non-adherence to medication and recommendations, and to test whether increased adherence improved HRQoL in patients after myocardial infarction (MI) in a case management intervention. Methods Data were obtained from the intervention group of the KORINNA study, a randomized controlled trail of a nurse-led case management intervention with targeted recommendations in the elderly after MI in Germany. Reasons for non-adherence were described. Logistic mixed effects models and OLS (ordinary least squares) were used to analyze the effect of recommendations on the probability of adherence and the association between adherence and HRQoL. Results One hundred and twenty-seven patients with 965 contacts were included. Frequent reasons for non-adherence to medication and recommendations were “forgotten” (22%; 11%), “reluctant” (18%; 18%), “side effects” (38%; 7%), “the problem disappeared” (6%; 13%), and “barriers” (0%; 13%). The probability of adherence was lowest for disease and self-management (38%) and highest for visits to the doctor (61%). Only if patients diverging from prescribed medication because of side effects were also considered as adherent, 3-year medication adherence was associated with a significant gain of 0.34 quality-adjusted life years (QALYs). Conclusions Most important determinants of non-adherence to medication were side effects, and to recommendations reluctance. Recommended improvements in disease and self-management were least likely adhered. Medication adherence was associated with HRQoL. Trial registration Current Controlled Trials ISRCTN02893746, retrospectively registered, date assigned 27/03/2009.